Yahoo! Pipes - Pruett, Mark (O'Reilly short cut., 2007)
The Internet is transforming itself froma collection of web pages into a huge distributeddatabase. There's a wealth ofdata out there-not just RSS and Atomfeeds, but XML data on where to find anew apartment, how much to pay for anew car, how to see if there's a storm approaching. If the Internet is your newdatabase, you need a tool to mine thatdata-to merge and sort and search andfilter that data. That tool is Yahoo! Pipes. Widely touted as an RSS feed aggregator, Yahoo! Pipes is more than that. WithYahoo! Pipes you can manipulate virtuallyany web-accessible XML datasource, and then publish these.